The Behavior of the Balance of Payments in the Different Monetary Regimes that have Existed in Ecuador - Salgado Defranc, Eddy José (2013)
The deficit in the balance of payments is a symptom that in the economy of a country there is an excess of means of payment in circulation. When we refer to countries with their own currency, this sign denotes that inorganic money issuances are taking place and that it is necessary to apply stabilization policies. In the case of Ecuador, it is a symptom of high public spending. Thus, austerity policies are required that would have the advantage of allowing the State to create a reserve to face possible external shocks to the economy, as a large number of countries in the world have.